BUSINESS PROCESS ANALYSIS IN THE ROSAN BAKERY BUSINESS UNIT - Muhammad Hilmi Fauzan (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2021)
Rosan Bakery's business unit is one of the intermediate bakeries and cakes in the city of Purwakarta which has high market potential. This can be seen from Finance Rosan Bakery which is categorized as good because the annual income has increased in the past five years. However, in 2021 there was a decrease in revenue of 6.03% from 2020. This decrease occurred due to the decline in the performance of Rosan Bakery and the problems and constraints that occurred in their business processes. This study aims to analyze the business process from Rosan Bakery, knowing any problems and constraints that arise in the process of Rosan Bakery's business, knowing the size of the performance of Rosan Bakery, analyzing data and concluding the right problem solutions to improve the business process of Rosan Bakery and utilize technology Information is more optimal for the business process of Rosan Bakery. The design of this study is qualitative research. The data collection method includes observation, interviews and literature studies. Data sources in the form of primary data and Skunder data. The analysis is carried out in accordance with the method chosen at each stage of increasing business processes. The results of the analysis show that promotion is a process that must be improved. The solution to increase the promotion of Rosan Bakery is to create a website indicated for e-commerce as the face of the promotion of Rosan Bakery. Keywords: Business process analysis, e-commerce, promotion, business processes